Thematic analysis of COVID-19's impacts on transitions among emerging adults - Keely H. Bieniak; Helen Bedree; Nicole Geanous; Rachel Neff Greenley; Steven A. Miller; Joanna Buscemi; Susan T. Tran (Health Care Transitions, 2024)
Objectives: This study explored how the COVID-19 pandemic impacted emerging adults. Previous COVID-19 research with this age demographic has focused on specific facets of life transitions (e.g., academic or economic stress) but does not consider the interrelatedness of these life domains. This project fills this gap by allowing participants to report on any aspects of their life to better understand frequent challenges with and experiences that may have helped with managing “the new normal” of the COVID-19 pandemic amidst typical transitions of emerging adulthood. Methods: Qualitative and quantitative data gathered in July 2020 (n = 145) and January 2021 (n = 143) as part of a longitudinal study of emerging adults (18–24 years) who were enrolled at a Midwestern United States University at baseline were analyzed to explore impacts of COVID-19, particularly in relation to stress. Results: Qualitative results demonstrate a range of negative COVID-19 effects, including health challenges and relationship strain. Interestingly, positive effects were also reported, including allocating more time for hobbies and spending quality time with loved ones. Quantitative findings indicate that COVID-19 distress did not increase over time, but perceived exposure to pandemic effects significantly increased. A general perceived distress measure demonstrated a slight decrease in distress over time, suggesting a potential adjustment to ‘the new normal.’ Discussion: COVID-19 impacted multiple domains of typical developmental transitions for many emerging adults in our sample. Individual qualitative reports demonstrate uniquely personal impacts of COVID-19, while thematic trends appear across responses (e.g., relationship strain). Health care providers must consider how these impacts influence the wellbeing of emerging adults with whom they work as the pandemic continues to evolve.